Factors Related to Preschoolers’ Snack Consumption Behaviour - wangnun, nuntinee; Piaseu, Noppawan (Journal of Thailand Nursing and Midwifery Council, 2018)
Abstract: Objective: To examine preschoolers’ snack consumption behaviour and its relation to individual factors (i.e., knowledge of and attitude towards snack consumption, daily allowance, and nutritional status); family factors (i.e., parents’ occupations and education, family’s income, and parents’ snack consumption behaviour); and socio-environmental factors (i.e., access to snack-related information, and the number of snack shops near the school and home). Design: Descriptive correlational research. Methodology: Through stratifed random sampling, a total of 154 pairs of preschoolers aged 5-6 and their guardians, all living in Muang district, Khonkaen province, were selected. Data were collected using a questionnaire, an interview, and nutritional state assessment. The data were analysed using descriptive statistics, Spearman’s correlation analysis and chi-square test. Results: The preschoolers’ average scores on snack consumption knowledge, attitude and behaviour were 67.7%, 39.7% and 53.8%, respectively. The majority of them consumed snacks more than once a week, the most frequently consumed types of snacks being crisps and chocolate, and the least frequently consumed being jelly. A correlation analysis revealed a negative relation between the preschoolers allowances and their snack consumption behaviour (rs = -.266, p = .001). On the other hand, a positive relation was found between the preschoolers snack consumption behaviour and their parents’ (rs = .632, p < .001). Recommendations: Based on the results, nurses and healthcare staff can apply the infomation for study on factors predicting consumption, and to developing a programme that properly promotes snack consumption behaviour of preschoolers, especially those on high daily allowances.